IMPROVING ABILITY TO OBSERVE STUDENTS OF CLASS II SDK GAMALIEL THROUGH HANDS ON ACTIVITY METHODS - Sarce Telussa; Galih Dani Septian Rahayu (IKIP Siliwangi, 2018)
This classroom action research was carried out by applying the hands on activity method to improve observing abilities. Through hands on activity will be formed an appreciation and experience to establish an understanding, because it is able to teach together cognitive, affective, and psychomotor abilities and can provide a deep appreciation of what is learned, so that what is obtained by students is not easily forgotten. The research method used is classroom action research (CAR) in class II SDK Gamaliel. To find out how to improve the ability to observe, the instruments used were written tests, oral tests, and observations. Peneliatian conducted in two cycles, each cycle consists of four (4) steps of activity, namely planning, action, observation and reflection. Before the first cycle begins with observation activities to determine the condition of learning and the ability to observe students. Cycle I actions as an effort to improve conditions that are stated as lacking or not yet complete in observation. Cycle II activity, an effort to improve / improve the situation that is still lacking in cycle I. The results of the study show that by using the hands on activity model the ability to observe SDK Gamaliel students increases.